Effects of traditional fitness qigong exercise on frailty status and overall well-being in frail or pre-frail patients: a systematic review and meta-analysis - Weijing Sun; Weijing Sun; Lingling Li; Zhenzhen Zhang; Xiuli Duan; Juanjuan Wei; Kim Lam Soh (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to assess the effectiveness of traditional Chinese Fitness qigong exercises (TFQs) in enhancing outcomes such as frailty status, physical function, psychological well-being, cognitive function, negative emotions, and sleep quality for older adults with frailty or pre-frailty.MethodsWe conducted searches in Embase, Cochrane Library, PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang, Chinese Technical Periodicals (VIP), and Google Scholar from their inception to 30th July 2024. Two reviewers independently selected and screened the papers, extracted the data, and assessed the bias risk. We used Review Manager 5.4 for data analysis, pooling the mean difference (MD) or standardized mean difference (SMD) through either random-effects or fixed-effects meta-analysis, depending on the level of heterogeneity.ResultsEighteen randomised controlled trials were included. A total of 15 studies, with 899 participants and versatile assessment tools (Fried Phenotype, Frailty Index, Tilburg Frailty Indicator), demonstrated the effectiveness of TFQs in reducing frailty. Subgroup analysis revealed significant improvements using FP scores (MD = −1.83, 95% CI: −2.09, −1.5), TFI (MD = −1.08, 95% CI: −1.22, −0.94), and FI (MD = −0.04, 95% CI: −0.08, −0.0). Physical performance improved significantly (MD = −0.72, 95% CI: −0.88, −0.57), while daily living activities showed no statistically significant changes (SMD = −0.20, 95% CI: −0.52, 0.11). Balance ability, including dynamic (MD = −2.55, 95% CI: −2.88, −2.22) and static balance (MD = 3.51, 95% CI: 3.00, 4.02), demonstrated notable enhancements. Grip strength increased significantly (SMD = 0.76, 95% CI: 0.51, 1.02), while gait speed improvements were more consistent in shorter walking distances (4.5 m: MD = − 1.44, 95% CI: −1.66, −1.22) than longer ones. Cognitive function (MD = 2.34, 95% CI: 0.35, 4.33) and sleep quality (SMD = 1.28, 95% CI: −1.69, −0.87) also exhibited substantial improvements. Quality of life (SMD = 1.17, 95% CI: 0.92, 1.42) and reductions in negative emotions (SMD = −0.79, 95% CI: −1.36, −0.22) were statistically significant.ConclusionTraditional Chinese Fitness qigong exercises (TFQs) significantly improved multiple outcomes for frail or pre-frail older adults, including frailty levels, physical performance, grip strength, balance ability, cognitive function, sleep quality, and quality of life. These results suggest that TFQs protect frailty or prefrail older adults.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024555719; Identifier: CRD42024555719.